Strategi Supervisi SDM untuk Meningkatkan Profesionalisme Guru PGSD di Sekolah Dasar - Yoserizal, Yoserizal; Jaya, Indra; Erlina, Erlina; Marlinda, Marlinda; Marsidin, Sufyarma; Rifma, Rifma; Sulastri, Sulastri (Journal of Educational Administration and Leadership, 2025)
Abstract This study, titled "Human Resource Supervision Strategies to Improve the Professionalism of Elementary School Teachers from PGSD Programs," aims to explore how systematic and evidence-based supervision strategies can enhance the pedagogical professionalism of pre-service primary school teachers. The background of the study is based on the growing demand for competent and adaptive educators in the 21st century, highlighting the urgency for supervisory approaches that go beyond administrative compliance. Recent empirical studies indicate that innovative instructional models, such as open inquiry-based learning and the Concentrated Language Encounter (CLE) method supported by short films, significantly improve students’ conceptual understanding and literacy skills. These findings suggest that HR supervision must be transformative, collaborative, and focused on continuous pedagogical development. This research adopts a Systematic Literature Review (SLR) approach to comprehensively analyze and synthesize existing studies related to human resource supervision in teacher education. A total of 500 scholarly articles were reviewed using inclusion and exclusion criteria focused on supervision practices, teacher professional development, and innovative learning strategies in primary education. After rigorous screening and quality appraisal, 11 relevant articles were selected for synthesis. The results indicate that effective HR supervision strategies—integrating mentoring, reflective practices, and sustained training—are essential to develop professional, independent, and contextually responsive PGSD teachers. These findings provide a strong basis for policy formulation and practical implementation in Indonesian primary education settings.